Lung volumetry of osteogenesis imperfecta type 3 subjects is not correlated with thoracic scoliosis and anthropometric data - Lopez-Beneyto, Jorge; Ponte, Elisabetta; Martínez-Sanjuan, Vicente; Fernandez-Velilla, Maria; Mata-Escolano, Federico; Torres-Sanchez, Maribel; García-Río, Francisco; Nalla, Shahed; Ercan, Ilker; Sanchis-Gimeno, Juan A. (Orphanet journal of rare diseases, 2025)
This study aimed to investigate the relationship between lung volumetry, thoracic scoliosis, and anthropometric data (height, weight, BMI) in patients with Osteogenesis Imperfecta (OI) Type 3. Three hypotheses were tested: H1 predicted lower lung volumes in patients with OI Type 3 compared to controls, H2 predicted differences between right and left lung volumes in patients with OI Type 3 due to chest deformities, and H3 predicted a correlation between lung volumes in patients with OI Type 3 and their thoracic scoliosis and anthropometric data. Age, biological sex, weight, height, body mass index (BMI), Cobb angle of thoracic scoliosis, left and right lung volumes, and total lung volume were recorded. CT scans were performed on all participants, and lung volumetry was analysed using specialised software. The intraclass correlation coefficient was used to assess measurement reliability, and statistical analysis was conducted to examine correlations between variables. Patients with OI had significantly lower total lung volumes than controls (p < 0.001). However, no significant correlation was found between lung volumetry and scoliosis (r =- 0.406; p = 0.244), age (r = 0.201; p = 0.578), height (r = 0.479; p = 0.162), weight (r = 0.358; p = 0.310), or BMI (r = - 0.042; p = 0.907) in OI patients. In the control group, significant correlations were observed between lung volume and height (r = 0.756; p = 0.011) and weight (r = 0.638; p = 0.047). OI type 3 patients have lower lung volumes than healthy subjects, but have no left and right lung volume differences. In addition, they did not present any correlation between lung volumes and scoliosis, height, weight, and body mass index.